Keragaan Adopsi Teknologi Inseminasi Buatan (IB) Kambing di Kecamatan Andoolo Kabupaten Konawe Selatan - Witjaksono, Julian (Department of Agribusiness, Halu Oleo University, 2020)
Goat farming system has long been carried out by farmers in Indonesia, is the essential farm for smallholder farmers, especially in rural areas as the cash money for income generation. However, farmers have been facing reproductive inefficiency and low meat productivity. Therefore, Artificial Insemination technology has been implemented for genetic improvement of goats in order to increase the sale value of livestock, increasing livestock productivity, and to accelerate genetic gain in local goat. This study was conducted to find the performance of the implementation of AI technology using Boer frozen semen. This study was carried out in Bina Marwa Village and Mata Up Village Andoolo Sub District, South Konawe District of Southeast Sulawesi Province in 2018. Study findings show that the farmer assessment of implementing AI technological innovation based on these innovations in terms of profits, compatibility, easily implementing, triability, and observability indicated a good percentage (59.87%), quite good (11.87%) and not good (28.26%). In addition, this technology has been deployed across the village and rapidly adopted among the farmers due to the low-cost of introducing AI technology, and the better physical appearance of genetic improvement (100%), respectively. Another driving factor was favorable AI technology (80%) and that is easily applied (60%).